Sphingomyelin synthase inhibitors from edible mushrooms prevent overweight and improve vitamin D homeostasis in a mouse model of diet-induced obesity - Enkhbat, Enkhmaa; Murai, Yuta; Yuyama, Kohei; Sun, Hui; Swamy, Mahadeva M. M.; Suga, Yoshiko; Anetai, Masaki; Monde, Kenji (Frontiers in Nutrition, 2025)
IntroductionSphingomyelin synthase (SMS) is a key enzyme in sphingolipid metabolism that converts phosphatidylcholine and ceramide into sphingomyelin and diacylglycerol, thereby influencing lipid signaling and metabolic regulation. Identifying natural SMS inhibitors is of interest for the prevention and management of obesity and related disorders.MethodsWe screened more than 860 extracts from medicinal plants and mushrooms using a cell-based assay for SMS inhibition. Active fractions were purified, and grifolin and grifolic acid were isolated from the edible mushroom Albatrellus confluens (Alb. & Schwein.) Kotl. & Pouzar and structurally confirmed. Their inhibitory activity was validated in vitro against sphingomyelin synthase 1 (SMS1) and sphingomyelin synthase 2 (SMS2), and their metabolic effects were tested by dietary supplementation (0.1% in high-fat diet) in male C57BL/6J mice for 9 weeks.ResultsBoth compounds inhibited SMS activity at low micromolar concentrations. In vivo, they significantly reduced body weight gain, improved glucose tolerance, and alleviated hepatic steatosis in high-fat diet–fed mice. Treatment also preserved circulating 25-hydroxyvitamin D₃ [25(OH)D₃] concentrations and downregulated hepatic expression of the vitamin D–catabolizing enzyme CYP24A1.ConclusionThese findings demonstrate, for the first time, that mushroom-derived metabolites can act as dual-substrate SMS inhibitors with beneficial effects on lipid and vitamin D metabolism. Grifolin and grifolic acid thus represent promising candidates for development as functional food components or nutraceuticals to prevent obesity and metabolic syndrome.